Stage II cancer diagnosis using printed antenna implemented on hemispherical model for human breast - Ali, N.; Sree, Mohamed Fathy Abo; Uyguroglu, R.; Allam, A. M. M. A. (Iop Publishing Ltd, 2020)
In this paper electromagnetic properties of a female human breast are used for cancer diagnosis. Deviation of the malignant cells' properties from those of healthy cells' directly affect the performance of an antenna placed on the breast. Return loss, gain and directivity of an antenna designed on an FR4 substrate were used as parameters for studying the effects of normal and cancerous tissue. A hemispherical shaped breast model is presented covering the breast, skin, fat and part of the connected lymph nodes. Tumors in breast and lymph nodes with different sizes and numbers were used to illustrate the second stage of cancer diagnosis. The antenna was designed and fabricated, and return loss measurements were taken using a network analyzer. Separate measurements were taken in free space and when placed on a healthy human breast. The return loss was simulated using CST Microwave Studio for antenna implemented on normal breast models and it is in good agreement with those of the measured results. The presented work has shown to be a preliminary model way for breast cancer diagnosis thereby reducing the need for invasive surgical operations.
Keywords: Antennas; Microwave Antennas